2020
DOI: 10.3174/ajnr.a6646
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing White Matter Tract Organization in Polymicrogyria and Lissencephaly: A Multifiber Diffusion MRI Modeling and Tractography Study

Abstract: BACKGROUND AND PURPOSE: Polymicrogyria and lissencephaly may be associated with abnormal organization of the undelying white matter tracts that have been rarely investigated so far. Our aim was to characterize white matter tract organization in polymicrogyria and lissencephaly using constrained spherical deconvolution, a multifiber diffusion MR imaging modeling technique for white matter tractography reconstruction. MATERIALS AND METHODS:We retrospectively reviewed 50 patients (mean age, 8.3 6 5.4 years; range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…e shows a single ventral TPF (arrow), and the CST (arrowhead) is located behind the TPF. f-k also show CST (blue fiber) running behind the dorsum of the single TPF (red fiber) patients with LIS had more white matter tract abnormalities than patients with polymicrogyria [14]. Thus, DTI enables the detection of more anomalies than conventional MRI sequences in patients with MCD, including LIS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…e shows a single ventral TPF (arrow), and the CST (arrowhead) is located behind the TPF. f-k also show CST (blue fiber) running behind the dorsum of the single TPF (red fiber) patients with LIS had more white matter tract abnormalities than patients with polymicrogyria [14]. Thus, DTI enables the detection of more anomalies than conventional MRI sequences in patients with MCD, including LIS.…”
Section: Discussionmentioning
confidence: 98%
“…DTI analysis of LIS and related disorders has been reported in several studies. Arrigoni et al analyzed DTI findings of 15 patients with brainstem malformations associated with the tubulin gene family and reported that asymmetries between the two sides of the brainstem appeared to be related to asymmetries in the thickness of the major white matter tract [14]. Dobyns et al described a case of an MACF1 mutation patient who showed absence of the anterior and posterior TPF on a color map [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, constrained spherical deconvolution (CSD) is better performed at higher b-value and diffusion encoding directions than those performed in the present study. Yet, CSD at b = 1000 and diffusion directions = 32 has shown to be reliable [51] and adequate to investigate white matter in clinical study [52]. This is the first preliminary pilot study to investigate WM changes underlying tDCS.…”
Section: Limitationsmentioning
confidence: 90%
“…This multi-shell multi-tissue CSD technique is used growingly, providing more reliable fODF information for tractography. It is now also possible to perform reliable local multi-tissue CSD estimations using either a single-shell HARDI data (Dhollander and Connelly 2016), or a single-shell, non-HARDI dataset consisting of a lower b-value and/or lesser diffusion directions (Calamuneri et al 2018, Arrigoni et al 2020, Fekonja et al 2021. Of note, the tractography examples shown in figure 6 were reconstructed using the multi-tissue CSD model.…”
Section: Methods For Deriving Fodfmentioning
confidence: 99%